Translation Method and Quality of Encanto’s “We Don’t Talk about Bruno” Song Lyrics - Aryl Timothy Madilah; Deta Maria Sri Darta (UIN Raden Mas Said Surakarta, 2026)
Translating song lyrics which are intended to be sung is challenging, and translators need to strive for a rendering that can achieve this goal. This study examined the method and the quality of the Indonesian translation of “We Don’t Talk about Bruno”, a popular song from Disney’s Encanto. It incorporated Newmark’s theory on translation methods and translation procedures in identifying the method used to render the song lyrics, and Low’s Pentathlon Principle in assessing the quality of the translation. The study was qualitative, where the song was analyzed line by line, first to determine the procedures, and second with the help of participants by means of interview to determine the quality. Thereafter the method and the overall quality were determined. The result showed the communicative method as the translation method, with preference for multi-procedures per line mainly of literal, modulation, and reduction procedures. The quality of the rendering was standard, with high preference towards Singability, Naturalness, and Rhythm. This exhibited how translators look for fitting the target text to its purpose of being singable, and reinforced the notion of compensating things such as the sense and rhyming pairs of the song in order to achieve the goal.